AWARENESS ON DISPOSAL OF LIQUID WASTE IN DENTISTRY AMONG DENTAL STUDENTS - Gurumurthy, Kaviyaselvi; Ganapathy, Dhanraj; Sasanka, Keerthi (International Journal of Psychosocial Rehabilitation, 2025)
Despite the advancing technological methods to prevent diseases, outbreaks become more common due to the ineffective waste disposal methods followed in dental clinics. In safe and effective disposal of wastes, the key step is the separation or segregation of the wastes produced depending on its nature and composition. The present study aims at determining the awareness on safe disposal of liquid dental waste among undergraduate dental students. For the study, a pre tested questionnaire consisting of 10 questions assessing the awareness and knowledge about waste disposal of liquids in dental clinics was prepared and circulated to a total of 100 undergraduate dental students of varying age groups via an online survey planet link. The responses provided by the students were collected, diagrammatically represented and analysed to determine the comprehension levels and understanding on the type of waste disposal system implemented and followed in the respective dental clinics. In addition to this, the requirement to layout a proper apprehension on the same was monitored.94% of the population are aware of the waste produced in the dental industry ,72.% of individuals believed that more than 2 liters of liquid waste are produced on an average daily basis. 53% of populationwere aware that mercury was one of the essential components of liquid waste. 85%, who felt that the wastes produced had to be separated before disposal. 89% of the population were aware that dental wastes affect the people living around the disposal area and 71% felt that dental wastes could be recycled.The knowledge and awareness levels among dental students was adequate on the different types of liquid wastes produced in dental clinics and the effective solution to minimize this waste and dispose them safely. Further, the results of the survey conducted were educated the need and necessity to inculcate the correct management techniques of dental wastes and to make dental students realise the importance of this subject.